INTENSITAS CAHAYA, PENGARUHNYA TERHADAP PERTUMBUHAN DAN LAJU SINTASAN LARVA KERAPU TIKUS (Cromileptes altivelis) EFFECT OF LIGHT INTENSITY ON GROWTH AND SURVIVAL RATE OFPOLKA DOT GROUPER (Cromileptes altivelis) - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2000)
ABSTRACT: The study was conducted to know the effect of light intensity on relative growth in length and survival rates of the grouper larvae (Cromileptes altivelis). The study was to indicate the optimum light intensity that could maximize relative growth in length and survival rate of the grouper larvae. The study used completely randomized design (CRD) of four treatments with three replicates, as follows : light intensity 0 lux, 300 lux, 600 lux and 1200 lux. The first illumination was given at the late afternoon of day -2. The experiment used 40 I capacity tank and stocked with eggs at density of 30 pcs/I. The total length, survival rate, behaviour, water quality and development of larvae were examined. The result showed that the highest relative growth in length at the day-15 (87.54 %) was observed in light intensity 600 lux, followed by 1200 lux (76.10%), 300 lux (64.89%) and 0 lux (48.86%). The survival rates of light intensity 600 lux at the day-15 (8.46%) the highest, followed by 300 lux (6.22%), 1200 lux (4.57%) and 0 lux (3.74%). The study pointed out, different of light intensity showed significantly different effects (P 0,01) on the relative growth in length and survival rate of grouper larvae. The effects of light intensity on the relative growth in length to follow equation Y = 46.714 + 0.098X â 6.000- X2 (R2 -- 0.9356), whereas the effect of light intensity on the survival rate to follow equation Y = 3.516 + 0.014X â 1.000-5X2 (R2 = 0.9581). The maximum relative growth in length of the polka dot grouper till day-15 was at light intensity 815 lux and maximum survival rate was at ligth intensity 701 lux.